Kleptopia : how dirty money is conquering the world - Burgis, Tom. (London : William Collins, 2020)
They are everywhere, the thieves and their people. Masters of secrecy. Until now we have detected their presence only by what they leave behind. A body in a burned-out Audi. Workers riddled with bullets in the Kazakh desert. A rigged election in Zimbabwe. A British banker silenced and humiliated for trying to expose the truth about the City of London. They have amassed more money than most countries. But what they are really stealing is power. In this real-life thriller packed with jaw-dropping revelations, award-winning investigative journalist Tom Burgis weaves together four stories that reveal a terrifying global web of corruption: the troublemaker from Basingstoke who stumbles on the secrets of a Swiss bank, the ex-Soviet billionaire constructing a private empire, the righteous Canadian lawyer with a mysterious client, and the Brooklyn crook protected by the CIA. Kleptopia follows the dirty money that is flooding the global economy, emboldening dictators and poisoning democracies. From the Kremlin to Beijing, Harare to Riyadh, Paris to the White House, it shows how the thieves are uniting - and the terrible human cost. While we are looking the other way, all that we hold most dear is being stolen.
Keywords: Political corruption; Corruption; Money laundering